The Characteristics of Organizational Culture on Teacher Performance in Schools - Hasrul Azwar Hasibuan; Rindi Andika (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
The characteristics of organizational culture can have a significant impact on the performance of teachers in schools. Some characteristics of organizational culture that can influence teacher performance are as follows: task orientation, communication, social support, recognition, and learning culture. Research is conducted with a procedure or work stages starting from the preparation phase where the research team prepares a review of relevant theories related to the research being conducted, discussions, sharing of knowledge, and literature searches are activities in this phase. Then, initial observation is carried out on the problem, followed by submitting written questions to the respondents in the form of a questionnaire, and then the data is collected, tested, analyzed, and evaluated.